PREJUDICES ON CONCERNING HUMAN RIGHTS VIS-A-VIS ISLAM - Saruhan, Müfit Selim (SCAD Independent, 2020)
In the history of thought, defending human rights and freedom, positivist and materialist views are critical of religion in general and Islam in particular. Islam as a divine religion with its theoretical and practical dimensions has been the guarantor of human rights. Positivist and materialist views on every occasion ready to blame and identify the Islamic concept of servitude (to God) with slavery. But if we examine Islam in-depth with a philosophical mind, we can see that the Islamic concept of devotional servitude accommodates genuine freedom which intends to protect the health of both the body and the soul. Positivist and materialist minds consider the issue of human rights as their own, and religious sides approach this issue reluctantly due to the rhetoric of human rights devoid of religious rhetoric. Finding reasonable answers to the questions of what the source of human honor is and what makes human being meaningful will bring closer to each other the positivist/materialist views and religious views.